2016
DOI: 10.4047/jap.2016.8.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ozone and paracetic acid disinfection on adhesion of resilient liners to acrylic resin

Abstract: PURPOSEThe aim of this study was to evaluate the effect of paracetic acid (PAA) and ozone disinfection on the tensile bond strength (TBS) of silicone-based resilient liners to acrylic resins.MATERIALS AND METHODSOne hundred and twenty dumbbell shaped heat-polymerized acrylic resins were prepared. From the mid segment of the specimens, 3 mm of acrylic were grinded off and separated parts were reattached by resilient liners. The specimens were divided into 2 control (control1, control7) and 4 test groups of PAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…This result is in agreement with that reported by Ekren et al, 22 who found that prolonged exposure to ozone lead to a significant decrease in tensile strength; other studies have shown the mechanical properties of the resins were impaired as a result of storage in water for a long period. 32 The use of water may affect the mechanical properties of the acrylic resins and the prolonged exposure to water reduces the strength of the denture, which could be attributed to the brittleness of the resin and weakness of its tensile strength, as well as a loss of monomer by exudation and a decrease in mechanical properties when the denture base resin is conditioned for long periods.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with that reported by Ekren et al, 22 who found that prolonged exposure to ozone lead to a significant decrease in tensile strength; other studies have shown the mechanical properties of the resins were impaired as a result of storage in water for a long period. 32 The use of water may affect the mechanical properties of the acrylic resins and the prolonged exposure to water reduces the strength of the denture, which could be attributed to the brittleness of the resin and weakness of its tensile strength, as well as a loss of monomer by exudation and a decrease in mechanical properties when the denture base resin is conditioned for long periods.…”
Section: Discussionsupporting
confidence: 93%
“…Laboratory experiments, with the soft lining of the bonding forces denture base materials was carried out using different methods of testing by various researchers, for example shear, tensile or peel tests. [20][21][22][23][24][25][26] The tensile bond strength test has been extensively used by researchers. In this study, the tensile test method is preferred because it provides the surface of the draft; it can give information about the structure of the boundary layers and the location of the failures.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this study, immersion in 2.5 ppm of ozonated water for two hours per day did not affect the bond strength of Molloplast-B to acrylic denture base resin. Ekren and Ozkomur [21] studied the effect of peracetic acid and ozonated water on the tensile bond strength of two denture liners. They observed that prolonged exposure of Molloplast-B to ozonated water can adversely affect the bond strength; however, they used a higher concentration of ozonated water (4 ppm) compared to this study [21].…”
Section: Discussionmentioning
confidence: 99%